Cross-linked alginate-gelatine beads - Almeida, PF (2015)
This work is focused on the development of a new particulate drug delivery system using a sodium alginate matrix containing pindolol as a model drug molecule for intestinal drug prolonged release. Calcium alginate beads are known to be unable to control the release of most insoluble drugs. Pindolol-loaded alginate-gelatine beads have been developed using a solvent-free technique that involves a cross-linking reaction. Modifications in matrix structure and physicochemical behaviour caused by the cross-linking reaction were assessed during particle formation and drug release. Several parameters, such as matrix gelling rate, encapsulation efficiency, drug release profile and matrix erosion rate, were investigated. Physicochemical characterisation indicates the formation of a new alginate-gelatine matrix and shows that pindolol does not interfere with the matrix formation process. Matrix swelling of calcium alginate beads induced by phosphate buffer ends up in erosion and destruction. However, for cross-linked beads swelling does not lead to complete erosion, which may be the main cause of pindolol retention within the matrix. The modifications introduced in the initial calcium alginate formulation by means of an appropriate method such as the use of a cross-linking agent successfully changed the matrix performance, allowing the controlled release of pindolol. (C) 2004 Elsevier B.V. All rights reserved.